Implementasi Manajemen Masjid Dalam Memakmurkan Masjid Al-Huda Sukajati Haurgeulis - Sri Widartik; Ahmad Asrof Fitri; Meity Suryandari (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The implementation of mosque management is an activity that takes place in a mosque and refers to certain rules about mosque management. When running its business, the mosque always refers to a rule that has been set up and follows all of its rules. By following all of the mosque's rules, the mosque can do well. This is because the people in charge of mosques now talk to each other well. There are also things that help and things that hurt the management of a mosque. This study uses a method called